Brucellosis Outbreaks Associated with Domestic Consumption of Legally Imported Unpasteurized Goat Cheese—Dallas County, Texas, 2016. (4th October 2017) - Ward, Michelle; Stocks, Meredith; VanAuker, Loan; Richardson, Folasuyi; Chung, Wendy
Abstract: Background: Brucella infections associated with travel to endemic countries or imported unpasteurized dairy products continue to present public health challenges in the United States. Although less than 6 brucellosis cases are typically reported annually in Dallas County, a record of 25 brucellosis cases were diagnosed in 2016, primarily due to large outbreaks from imported unpasteurized cheese. Methods: In 2016, all Brucella clinical isolates one isolate from cheese were confirmed as B. melitensis by PCR and biochemical testing in the Dallas County laboratory. Case interviews and medical chart reviews were conducted to determine exposures and illness characteristics. Supplemental questionnaires were administered to assess knowledge and practices relevant to brucellosis and pasteurization. Results: In 2016, 20 confirmed and 5 probable brucellosis cases were reported in Dallas County. Twenty cases, including 2 residents in an adjacent county, were associated with one of 3 separate epidemiologic clusters linked to unpasteurized goat cheese purchased in Mexico, legally imported for personal use, and distributed domestically to friends and relatives. Of the 27 cases, all were Hispanic, 22% were less than 18 years of age (median age 39 years), 67% were male, and only 59% had recent international travel. Although 50% of interviewed adults demonstrated an understanding of pasteurization, 67% were unaware that the consumed cheese was unpasteurized, and 92% were unaware of any health risks associated with consuming unpasteurized cheese. All adults cited economic consequences of their illness, such as missing work (median 31 days) or significant medical costs (median $4, 000). Conclusion: These findings highlight the need to improve awareness about the health risks associated with consuming unpasteurized dairy products. Public health and healthcare providers should consider that brucellosis can occur in persons without travel history or who are unaware that they consumed unpasteurized food. Active public health follow-up conducted for these brucellosis clusters ensured: education of exposed persons with low English literacy rates, prompt referral of symptomatic patients to clinical care, and notification of evaluating clinicians and laboratories of a suspected diagnosis. Disclosures: All authors: No reported disclosures.